Relationship between Decrease in Serum Sodium Level and Bone Mineral Density in Osteoporotic Fracture Patients - Kwak, Mi Kyung (J Bone Metab, 2015)
BACKGROUND: Recently, it has been suggested that decrease in serum sodium level is associated with osteoporosis. However, no study in Korea has reported the association of decrease in serum sodium level with osteoporosis. In this study, we investigated the relationship between the decrease in serum sodium level and severity of osteoporotic fracture in patients. METHODS: We enrolled 290 subjects who were admitted and operated at Soonchunhyang University Hospital due to major fractures. For the control group, we enrolled 1,027 subjects who visited a health promotion center. We carried a 1:1 matching with age and sex from the case group. RESULTS: In a total of 164 age- and sex-matched subjects, serum sodium level was significantly lower in the fracture group than in the non-fracture group (P=0.001). Serum sodium level was significantly lower in the severe osteoporosis group than that in the non-severe osteoporosis group (P=0.002). Old age and decrease in serum sodium level were independent risk factors of osteoporosis (odds ratio [OR]=1.088, P=0.008, confidence interval [CI]=[1.022-1.157]; OR= 0.840, P=0.037, CI=0.713-0.989). CONCLUSIONS: Serum sodium level was significantly lower in the fracture group than that in the non-fracture group and in the severe osteoporosis group than that in the non-severe osteoporosis group. Based on our results, the decrease in serum sodium level could be an independent risk factor for osteoporosis.